Rodents density at food premises in Kajang Selangor / Mohd Asrul Ahmad - Ahmad, Mohd Asrul (Faculty of Health Sciences, 2015)
This study was conducted at Pusat Hentian Kajang and Section 15 Bandar Baru Bangi in Kajang, Selangor. The study involved Ready to Eat (RTE) food premises at commercial area. The total of RTE food premises involved in this study (n=20). The study design of this study is cross-sectional study. Rodent’s infestation at indoor RTE food premises and factor’s that attract rodent’s infestation were obtained. The caught rodents (n=29) species were identified based on their physical appearance and ectoparasites were collected by combing. The analysis of rodent species caught shows Rattus norvegicus (n=29) and none other species was caught by live trap. The total catchment at Pusat Hentian Kajang RTE food premises (n=12), while for the Section 15 Bandar Baru Bangi RTE food premises (n=17). None Xenopsylla cheopis were obtained on Rattus norvegicus, but other type of ectoparasite was found on caught rodents (n=5,17.24%). Total ectoparasite index presence on rodent is 0.172 (<1). Food premises inspection was conducted at the selected RTE food premises at both area. The rating’s mark was between 50.6% to 90.8% when the study’s inspection was carried out. In conclusion, the detection of rodents and it’s infestation at indoor RTE food premises will increase risk to public health. The effective rodent’s control must conducted to minimize the density of rodents at the both areas